The Strategies of the Company to Step in The Fuel Business in Indonesia - Taha, Richard Yauri (UI Scholars Hub, 2011)
The Law No. 22 of 2001 provides opportunities for private companies to step in the fuel business. PT. AKR Corporindo Tbk sees the fuel business in Indonesia as an opportunity based on the available resources. The purpose of this research is to analyze the company’s strategies to take the opportunity of stepping in the fuel business in Indonesia, using the approaches of entrepreneur school, creative destruction, and innovation analysis. This research is descriptive and uses qualitative approach. The data were collected through observation, literary study, and in-depth interviews. The result of this research shows that AKR Corporindo Tbk has taken benefit of stepping in the fuel business in Indonesia. This research reveals the fuel business in Indonesia as well as decision making in the business strategies.